Masculinidades no reino de deus: corpo, gênero e representações sociais de homem entre frequentadores da igreja universal do reino de deus - Alberto Mesaque Martins (2019)
Brazil is one of the most religious countries in the world, composed of diverse religions that attract, daily, thousands of people throughout the national territory. Without disregarding their potential of connecting members with a transcendent dimension, religions also constitute a space of interaction and sociability, where beliefs, attitudes, and values related to different subjects of everyday life can circulate. Through dogmas and rituals, religious institutions (re)produce socially shared knowledge that guide how their members should behave, regarding both religious life and secular life. Therefore, it is an important object of analysis in Social Psychology. Different studies show the importance of religious beliefs and practices for the (re)production of conceptions on masculinity, revealing that these institutions contribute to the production and diffusion of representations and norms that guide members in the use of their masculinity. In this context, we find the Universal Church of the Kingdom of God (UCKG), which, among the Brazilian neo-Pentecostal churches, has been highlighted not only by the growing number of members, congregated in temples throughout the national territory, but also by the prominent place that this institution occupies throughout its history, both in the Brazilian political scene and in the vehicles of mass communication, producing strategies that seek to guide the way its members exercise their femininity and masculinity. Based on the assumptions of Social Psychology, especially on the Theory of Social Representations developed by Serge Moscovici and Denise Jodelet, the main objectives of this study are to identify and analyze the Social Representations of men constructed and disseminated among UCKG members and to analyze the implications of the experience of conversion to neo-pentecostalism in the processes of masculine identity construction. The corpus of the thesis consists of three distinct but interrelated studies. The first article presents an integrative review of the international scientific production, available in the SciELO, PePSIC and Lilacs databases, between 2005 and 2016, on the sociocultural aspects that pertain to the construction of male body image. Then, in the second article, it has been sought to identify and analyze the social representations of men in the context of the “IntelliMen Project”, which exists exclusively for men who attend UCKG. At this stage, a Documentary Survey was conducted on the IntelliMen project manual, named "IntelliMen: 53 Challenges for Smart Men". Finally, the third article aims to identify and analyze the social representations of men constructed and disseminated among UCKG visitors and also to analyze the implications of the conversion experience in the processes of male identity construction. In order to do so, interviews were conducted with 12 men, all UCKG members. Analyzing the set of studies developed in the investigative process of this thesis, it is possible to observe that, despite the constant changes in society, masculine and feminine roles included, there are still ideas that contribute to the diffusion and maintenance of the model of hegemonic masculinity. In this perspective, the religious context also constitutes an important space for the diffusion of representations, attitudes, and beliefs that guide members in the use of their masculinity. Thus, after their conversion, the participants found themselves in need of reorganizing their conceptions, perceptions, values, and representations about themselves and about different aspects of their daily life, so that they could put into practice the dogmas and the religious teachings of the new group to which they, now, belong. Through actions and projects such as IntelliMen, men are pressured to transform themselves, denying the "Common Man" and searching for the image of an "IntelliMan". Given the aforementioned context, it takes a deliberate effort by newly converted men to "kill their old self" and engage in a process of radical transformation of their personal and collective identity. It is worth noting that this is not a matter of construction of a new model of masculinity, produced in the neo-Pentecostal religious context. The results of this investigation reveal that the social representations of men (re)produced in the context of the UCKG are strongly anchored in the hegemonic masculinity model, thus, being based on the same idealized and demanded attributes of men in the secular sphere.